Fine-Tuning of Smad Protein Function by Poly(ADP-Ribose) Polymerases and Poly(ADP-Ribose) Glycohydrolase during Transforming Growth Factor β Signaling - Dahl, Markus (Public Library of Science, 2014)
BACKGROUND: Initiation, amplitude, duration and termination of transforming growth factor β (TGFβ) signaling via Smad proteins is regulated by post-translational modifications, including phosphorylation, ubiquitination and acetylation. We previously reported that ADP-ribosylation of Smads by poly(ADP-ribose) polymerase 1 (PARP-1) negatively influences Smad-mediated transcription. PARP-1 is known to functionally interact with PARP-2 in the nucleus and the enzyme poly(ADP-ribose) glycohydrolase (PARG) can remove poly(ADP-ribose) chains from target proteins. Here we aimed at analyzing possible cooperation between PARP-1, PARP-2 and PARG in regulation of TGFβ signaling. METHODS: A robust cell model of TGFβ signaling, i.e. human HaCaT keratinocytes, was used. Endogenous Smad3 ADP-ribosylation and protein complexes between Smads and PARPs were studied using proximity ligation assays and co-immunoprecipitation assays, which were complemented by in vitro ADP-ribosylation assays using recombinant proteins. Real-time RT-PCR analysis of mRNA levels and promoter-reporter assays provided quantitative analysis of gene expression in response to TGFβ stimulation and after genetic perturbations of PARP-1/-2 and PARG based on RNA interference. RESULTS: TGFβ signaling rapidly induces nuclear ADP-ribosylation of Smad3 that coincides with a relative enhancement of nuclear complexes of Smads with PARP-1 and PARP-2. Inversely, PARG interacts with Smads and can de-ADP-ribosylate Smad3 in vitro. PARP-1 and PARP-2 also form complexes with each other, and Smads interact and activate auto-ADP-ribosylation of both PARP-1 and PARP-2. PARP-2, similar to PARP-1, negatively regulates specific TGFβ target genes (fibronectin, Smad7) and Smad transcriptional responses, and PARG positively regulates these genes. Accordingly, inhibition of TGFβ-mediated transcription caused by silencing endogenous PARG expression could be relieved after simultaneous depletion of PARP-1. CONCLUSION: Nuclear Smad function is negatively regulated by PARP-1 that is assisted by PARP-2 and positively regulated by PARG during the course of TGFβ signaling.